Transnational Seriality. The Circulation of Italian Television Drama in Europe - Sascor, Lorenzo (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
Historically, Italian television seriality, like its European counterpart, has always been confined within national borders. Apart from a few rare exceptions, Italian television drama has seen limited circulation abroad, due to cultural, industrial, and economic reasons. However, over the past 15 years, increasing digitalization, the emergence of new distribution channels, and new industrial configurations have led to significant shifts in the circulation of national intellectual properties. In this context, pay TVs first, and later streaming platforms, have played a crucial role in pushing for a broader and more successful circulation of Italian serial narratives, often emphasizing their dual nature as both local and global works. This essay aims to analyze the circulation of contemporary Italian television series in Europe, focusing on both the industrial and cultural dimensions involved. Combining a media industry studies approach with an analysis of audience reception, examples of contemporary Italian serial narratives distributed abroad will be discussed, considering how their European circulation highlights their simultaneous identity as both local intellectual properties and transnational media objects.